Operational and structural A‐stage improvements for high‐rate carbon removal. (26th May 2020) - Wett, Bernhard; Aichinger, Peter; Hell, Martin; Andersen, Martin; Wellym, Lie; Fukuzaki, Yasuhiro; Cao, Ye Shi; Tao, Guihe; Jimenez, Jose; Takacs, Imre; Bott, Charles; Murthy, Sudhir
Abstract: Biosorption of organics is investigated at two sites in order to optimize operation and infrastructure for carbon removal and redirection in upstream, high‐rate processes. Sufficient process temperature and stable mixed liquor solids concentration were established as the key impact parameters for the process performance. Improved COD removal was achieved by either substantially enhanced aeration (elevated metabolic state) or by enhanced flocculation capability (dosed chemicals). Separation and thickening of organics are typically operated as continuous‐flow processes. The optimization of performance parameters led to a new A‐stage process named alternating activated adsorption. The AAA process is presented as a novel configuration linking biosorption and thickening capabilities in an alternating scheme without mechanical equipment. The performance data from its first trial indicate benefits from process dynamics including high organics capture rates and thickening capabilities reaching solid concentrations higher than 40 g(TSS)/L. COD removal could be increased further by adding biologically generated polymer, that is waste sludge from B‐stage. © 2020 Water Environment Federation Practitioners Points: Enhanced preliminary treatment helps to increase capacity and energy efficiency. Low RAS rates, SRT control, aeration, high temperatures, and metal dosing are key performance parameters for removal rates and energy efficiency. The Triple‐A process offers new possibilities for A‐stage in terms of performance increase and flexibility showing similar or better results compared with conventional A‐stage. Adding B‐sludge improved COD and nutrient removal rates. High preliminary removal rates of COD and N foster sidestream processes. Abstract : Process improvements leading to a new design for high rate activated sludge systems: The Triple‐A Process.